2016
DOI: 10.1002/humu.22969
|View full text |Cite
|
Sign up to set email alerts
|

CoNVaDING: Single Exon Variation Detection in Targeted NGS Data

Abstract: We have developed a tool for detecting single exon copy-number variations (CNVs) in targeted next-generation sequencing data: CoNVaDING (Copy Number Variation Detection In Next-generation sequencing Gene panels). CoNVaDING includes a stringent quality control (QC) metric, that excludes or flags low-quality exons. Since this QC shows exactly which exons can be reliably analyzed and which exons are in need of an alternative analysis method, CoNVaDING is not only useful for CNV detection in a research setting, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 22 publications
0
76
0
Order By: Relevance
“…Under such conditions, targeted NGS shows its advantages compared with Sanger sequencing of every single gene. It is also noteworthy that gross deletions or duplications were implied by NGS and confirmed by MLPA in three patients in our cohort using data-based algorithms[42] and would have been missed by traditional Sanger sequencing.…”
Section: Discussionmentioning
confidence: 86%
“…Under such conditions, targeted NGS shows its advantages compared with Sanger sequencing of every single gene. It is also noteworthy that gross deletions or duplications were implied by NGS and confirmed by MLPA in three patients in our cohort using data-based algorithms[42] and would have been missed by traditional Sanger sequencing.…”
Section: Discussionmentioning
confidence: 86%
“…A CNV analysis was performed with NGS data following the previously reported CoNVaDING method, which had been specifically developed for gene panel data at high-coverage and enables accurately single-exon detection 60 . Briefly, it uses the average coverage of each specified target to perform calculations starting from BAM files.…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
“…Finally, it performs a filtering step that renders the list with deletions and duplications. The method includes QC metrics that make it possible to distinguish high-quality from low-quality samples 60 .…”
Section: Materials/subjects and Methodsmentioning
confidence: 99%
“…CNV analysis of MPS data has resulted in the identification of several novel CNVs [23*, 25, 31, 32*, 49, 54*] and has shown that many genes can harbor CNVs. Comprehensive CNV detection is as important as comprehensive SNV detection and analysis and must be included in all analytic pipelines.…”
Section: Cnv Inclusion and Methodologymentioning
confidence: 99%
“…Comprehensive CNV detection is as important as comprehensive SNV detection and analysis and must be included in all analytic pipelines. Two new CNV detection methods based upon differential read depth have been reported [23*, 54*], which should make CNV incorporation into TGE+MPS workflows more widespread.…”
Section: Cnv Inclusion and Methodologymentioning
confidence: 99%